North America. - Rapkin, J. (John Tallis & Company, 1850)
Map shows Russian America [Alaska], British Territory, Greenland, the United States, Mexico, "Guatimala," and the "West India Islands" and areas of native inhabitants. Texas is shown without panhandle area. Includes illustrations: "Esquimaux dog-sledge," "Mounta Hekla," "Beavers," "Falls of Niagara," "Convoy of diamonds," "Ancient monument," "Mexico," "North American Indians," "Wapiti Deer," and "Cossacks." Relief shown by hachures. Scale [ca. 1:35,000,000].